Analisis Pengaruh Pengetahuan Kewirausahaan, Self Efficacy dan Karakter Wirausaha Terhadap Minat Berwirausaha (Studi Kasus Mahasiswa Universitas Dharmas Indonesia) - Eni Marlina; Yesi Gusteti; Dini Elida Putri (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
This study aims to analyze the influence of entrepreneurial knowledge, self efficacy and entrepreneurial character simultaneously and partially on entrepreneurial interest (case study of University of Dharmas Indonesia students).  This study uses quantitative methods with data collection using questionnaire. Data analysis techniques in this study using Validity Test, Reability Test, Correlation Analysis, Multiple Linear Regression Analysis, Classical Assumption Test, T Test, F Test and Determination Test (R2). Respondent population in this study were 683 respondents and the sample was 253. The results of this study indicate that partially (t test) entrepreneurial knowledge has a significant effect on entrepreneurial interest, self efficacy has a significant effect on entrepreneurial interest, entrepreneurial character has a significant effect on entrepreneurial interest and simultaneously (f test) entrepreneurial knowledge, self efficacy and entrepreneurial character have significant effect on entrepreneurial interest. The Adjusted R2 value is 0.644, means that all independent variables can affect 64.0% of the dependent variable. While the remaining 36.0% can be influenced by other factors not tested in this study